A Study on Relationship between Customer Satisfaction and Customer Loyalty in Apparels Retail Store: With Reference to Hyderabad - Geeta Kesavraj, Dr.; Ravichandra BS, Mr. (International Journal of Engineering and Technology, 2018)
Loyalty can be understood as faithfulness, dedication, commitment or devotion to a person, profession, institution, or product. Formation of loyalty is an extremely important but difficult philosophy and psychology to decode. Loyalty implies a feeling or an attitude of devoted attachment caused by affection. Such attachment makes a person feel responsible to persevere with relationship even in adverse times. However, loyalty in commercial relationships involving company and its customer denotes a subtly different meaning. Customer loyalty is a transpired from a simple measure of repeat patronage to a broadly interpreted and multidimensional construct. The customer loyalty can be considered as the sum total of customerâ€™s level of satisfaction and degree of the customerâ€™s emotional attachment with a company that constructs a state of willingly and consistently being in the relationship and ultimately translate into customer loyalty.Â In the above context the objective of the study is to examine the relationship between customer satisfaction and customer loyalty in apparel retail store in Hyderabad.Â Â Data were collected through questionnaire survey of 50 customers of retail store in Hyderabad.Â Â Regression model is employed to examine impact of various drivers of satisfaction on customer satisfaction and correlation model is employed to examine the relationship between customer satisfaction and customer loyaltyÂ Â